Chromosomal locations of U2 snDNA clusters in Megaleporinus, Leporinus and Schizodon (Characiformes: Anostomidae) - Ponzio, Júlia Chagas [UNESP]; Piscor, Diovani [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (Springer Nature, 2018)
The U small nuclear RNA (U snRNA) genes comprise a multigene family and are required for splicing of pre-mRNA. In this paper, we aimed to study the chromosomal location of the U2 snRNA gene in Megaleporinus, Leporinus and Schizodon species, which constitute interesting models for the study of repetitive DNA and genomic evolution in fish once the group comprises species with and without heteromorphic sex chromosomes. The all six species showed 2n = 54 chromosomes: Megaleporinus elongatus, Megaleporinus macrocephalus, Leporinus striatus, Leporinus friderici, Schizodon borelli and Schizodon isognathus. The U2 snDNA clusters were evident in only one medium-sized submetracentric pair in all analyzed species and this may represent a condition shared by Anostomidae family.
Keywords: Diploid number; FISH; Karyotype; Repetitive DNA